High-performance sports and women’s health in cyclical sports - Kogan O.S.; Galiullina S.D.; Yamilyova R.M.; Greb A.V. (Theory and Practice of Physical Culture, 2025)
Objective of studywas to explore the healthstatus of women in cyclicalsports(shortandlong-distancerunning, cross-country skiing, speed skating,swimming),highlyqualified athletes –"master of sports"and"master of sports of internationalclass", who regularlyparticipateincompetitions in the Republic of BashkortostanandRussia and havenoincome other thanwages a member of a sportsclub, a scholarshipfrom the FederalAgencyforPhysicalCultureandSports of the RussianFederationor the MinistryofPhysicalCultureandSports of the Republic of Bashkortostan. Methods and structure of the study. An in-depth medical and clinical and functional examination of 33 women of the main and 49 women of the control groups was conducted on the basis of the Republican Medical and Physical Education Dispensary of the Republic of Bashkortostan. The health status of women aged 19-28 years, with 3-5 years of experience in the national team of the Republic of Bashkortostan, was studied. Results and conclusions. There were no statistically significant differences in the overall prevalence of chronic noncommunicable diseases in 33 high–class athletes and 49 women in the control group, 87.8 cases per 100 examined were among cyclical sports athletes, and 55.1 cases per 100 examined in the control group.